Digital Decision Support for Perioperative Care of Patients With Type 2 Diabetes: A Call to Action - Jianwen Cai; Peiyi Li; Weimin Li; Xuechao Hao; Sheyu Li; Tao Zhu (JMIR Diabetes)
AbstractType 2 diabetes mellitus affects over 500 million people globally, with 10%‐20% requiring surgery. Patients with diabetes are at increased risk for perioperative complications, including prolonged hospital stays and higher mortality, primarily due to perioperative hyperglycemia. Managing blood glucose during the perioperative period is challenging, and conventional monitoring is often inadequate to detect rapid fluctuations. Clinical decision support systems (CDSS) are emerging tools to improve perioperative diabetes management by providing real-time glucose data and medication recommendations. This viewpoint examines the role of CDSS in perioperative diabetes care, highlighting their benefits and limitations. CDSS can help manage blood glucose more effectively, preventing both hyperglycemia and hypoglycemia. However, technical and integration challenges, along with clinician acceptance, remain significant barriers.